Pengembangan Game Quiz Interaktif Berbasis Canva pada Pembelajaran IPAS Materi Keragaman Budaya dan Kearifan Lokal untuk Siswa Kelas 4 SDN 1 Pinang Jaya - Sari, Epi; Sutiyono, Akhmad; Lestari, Yulita Dwi (STKIP PGRI Bandar Lampung, 2025)
The problems in this study include 1) the learning process rarely uses technology-based media, 2) the results of learning in science are still low, 3) learning is not yet centered on students, 4) the learning media used are not varied and 5) the use of interesting quizzes through interactive media has never been given. Through the development of interactive quiz games based on canva, it is expected to help teachers create interesting and fun learning and increase students' attention and interest in the learning process. The purpose of this study was to determine the level of feasibility, responses of educators and students and the effectiveness of interactive quiz games based on canva in science learning on cultural diversity and local wisdom for grade 4 SDN 1 Pinang Jaya. The type of research that will be used is R&D (Research and Development). This development research refers to the ADDIE model with five development steps, namely: 1) Analysis, 2) Design, 3) Development, 4) Implementation, 5) Evaluation. The instruments used are expert validation sheets, teacher and student response questionnaire sheets and pretest and posttest questions. The results of this development research indicate (1) the feasibility of the interactive quiz game based on Canva which produced 3 validations: material validation of 90%, language validation of 90% and language validation of 93.33%. The average of the 3 validations obtained a percentage of 91.11%, thus the media is included in the very valid qualification so that it is suitable for use. (2) the responses of educators and students in the development of this product include: (a) teacher responses obtained a percentage of 92% and (b) student responses in small-scale trials involving 8 people obtained a percentage of 91.07%, while in large-scale trials involving 24 people obtained a percentage of 90.60%. From the results of the teacher and student responses, it is included in the qualification of very practical and interesting to use. (3) the effectiveness of the media using the n-gain score calculation reached a percentage of 60.27%, which means that the results are included in the category of quite effective use in learning.